2013
DOI: 10.1128/jvi.01640-12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Complement on HIV-2 Plasma Antiviral Activity Is Intratype Specific and Potent

Abstract: Human immunodeficiency virus type 2 (HIV-2)-infected individuals develop immunodeficiency with a considerable delay andtransmit the virus at rates lower than HIV-1-infected persons. Conceivably, comparative studies on the immune responsiveness of HIV-1-and HIV-2-infected hosts may help to explain the differences in pathogenesis and transmission between the two types of infection. Previous studies have shown that the neutralizing antibody response is more potent and broader in HIV-2 than in HIV-1 infection. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…HSV-1 (Heineman, 1967;Friedman et al, 2000;Hook et al, 2006) HSV-2 (Heineman, 1967;Hook et al, 2006) EBV (Mold et al, 1988) HSV-2 (Gadjeva et al, 2004) Flaviviridae YFV (Schlesinger et al, 1985) -DENV (Avirutnan et al, 2010;Fuchs et al, 2010;Thiemmeca et al, 2016) WNV (Avirutnan et al, 2010;Fuchs et al, 2010) YFV (Avirutnan et al, 2010) HCV (Ishii et al, 2001) Retroviridae HIV-1 (Ebenbichler et al, 1991;Susal et al, 1994;Stoiber et al, 1996) HIV-2 (Ozkaya et al, 2013) HTLV-1 (Ikeda et al, 1998) -HIV-1 (Ezekowitz et al, 1989;Saifuddin et al, 2000) Togaviridae Venezuelan equine encephalitis virus (Brooke et al, 2012) Sindbis virus (Hirsch et al, 1980b) - (Reading et al, 1995) Paramyxoviridae Parainfluenza type 3 (Vasantha et al, 1988) Newcastle disease virus (Welsh, 1977) Measles (Sissons et al, 1979(Sissons et al, , 1980Devaux et al, 2004) Mumps (Hirsch et al, 1986;Johnson et al, 2008) NiV (Johnson et al, 2011) PIV (Vasantha et al, 1988) Sendai virus (Okada et al, 1979) Simian virus 5 (McSharry et al, 1981;Johnson et al, 2009) Mumps (Johnson et al, 2008) DENV (Avirutnan et al, 2011a),...…”
Section: Herpesviridaementioning
confidence: 99%
“…HSV-1 (Heineman, 1967;Friedman et al, 2000;Hook et al, 2006) HSV-2 (Heineman, 1967;Hook et al, 2006) EBV (Mold et al, 1988) HSV-2 (Gadjeva et al, 2004) Flaviviridae YFV (Schlesinger et al, 1985) -DENV (Avirutnan et al, 2010;Fuchs et al, 2010;Thiemmeca et al, 2016) WNV (Avirutnan et al, 2010;Fuchs et al, 2010) YFV (Avirutnan et al, 2010) HCV (Ishii et al, 2001) Retroviridae HIV-1 (Ebenbichler et al, 1991;Susal et al, 1994;Stoiber et al, 1996) HIV-2 (Ozkaya et al, 2013) HTLV-1 (Ikeda et al, 1998) -HIV-1 (Ezekowitz et al, 1989;Saifuddin et al, 2000) Togaviridae Venezuelan equine encephalitis virus (Brooke et al, 2012) Sindbis virus (Hirsch et al, 1980b) - (Reading et al, 1995) Paramyxoviridae Parainfluenza type 3 (Vasantha et al, 1988) Newcastle disease virus (Welsh, 1977) Measles (Sissons et al, 1979(Sissons et al, , 1980Devaux et al, 2004) Mumps (Hirsch et al, 1986;Johnson et al, 2008) NiV (Johnson et al, 2011) PIV (Vasantha et al, 1988) Sendai virus (Okada et al, 1979) Simian virus 5 (McSharry et al, 1981;Johnson et al, 2009) Mumps (Johnson et al, 2008) DENV (Avirutnan et al, 2011a),...…”
Section: Herpesviridaementioning
confidence: 99%
“…A study conducted by Ozkaya Sahin et al compared the effect of complement on HIV-1 and HIV-2. In this study they showed that a greater magnitude of the intratype anti-viral activity of samples from HIV-2-infected subjects was contributed by antibody-dependent complement-mediated inactivation (ADCMI) than in HIV-1 infection [81]. They further observed that the activation of the classical complement pathway through IgG is responsible for this effect.…”
Section: Antibody-dependent Complement-mediated Inactivation (Adcmi) mentioning
confidence: 77%
“…The spike on HIV-2 is reported to be more stable after budding [82], while in HIV-1 the number of spikes decreases after budding and maturation [83]. Since many of these spikes in HIV-1 are non-functional, the type of C1q-IgG binding required for the optimal effect of complement is low [81]. In addition, HIV-2 Env is more accessible and has a thinner glycan shield than HIV-1 [80].…”
Section: Antibody-dependent Complement-mediated Inactivation (Adcmi) mentioning
confidence: 97%
“…Furthermore, recent comparative studies on the immune responsiveness of HIV-1- and HIV-2-infected hosts have revealed that antibodies binding to HIV-2 structures facilitate the more efficient use of complement through activating the classical pathway than antibodies binding to HIV-1 and therefore may be one factor contributing to the strong antiviral activity elicited by HIV-2, but not HIV-1 (Ozkaya Sahin et al, 2013)…”
Section: Complement Activation In Hiv-infectionmentioning
confidence: 99%